2019
DOI: 10.1016/j.jfda.2019.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Viola cornuta and Viola x wittrockiana: Phenolic compounds, antioxidant and neuroprotective activities on Caenorhabditis elegans

Abstract: Different Viola species are known for their traditional use as analgesic, antitussive, febrifuge, hipnotic, analgesic and anti-inflammatory medicinal agents. Additionally, they are considered edible flowers in certain cultures. Thus, the aim of this work was to characterize the phenolic composition and to assess the neuroprotective properties of Viola cornuta and Viola x wittrockiana using in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 32 publications
4
27
0
Order By: Relevance
“…To further investigate the in vivo neuroprotective effect of rock tea, an examination was carried out as to whether diet supplementation may affect the progression of paralysis induced by Aβ toxicity in the C. elegans transgenic strain CL4176. This strain has proven to be a good model for screening potential neuroprotective natural products [ 15 , 22 , 23 ]. Nematodes were exposed to different concentrations of RT extract (5, 10 and 25 µg/mL) from the egg stage.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To further investigate the in vivo neuroprotective effect of rock tea, an examination was carried out as to whether diet supplementation may affect the progression of paralysis induced by Aβ toxicity in the C. elegans transgenic strain CL4176. This strain has proven to be a good model for screening potential neuroprotective natural products [ 15 , 22 , 23 ]. Nematodes were exposed to different concentrations of RT extract (5, 10 and 25 µg/mL) from the egg stage.…”
Section: Resultsmentioning
confidence: 99%
“…The accumulation of Aβ peptide caused by free radicals would result in neuron dysfunction and death. Different works have shown that phenolic compounds present neuroprotective activity, decreasing the deleterious effects of oxidative stress, increasing ACh availability, reducing the anti-inflammatory effect and interacting directly with Aβ peptides inhibit their aggregation and oligomerization [ 15 , 23 , 38 , 39 ]. The reduction of the IIS pathway and expression of genes as DAF-16, HSF-1, HSP-16 and Nrf2/SKN-1 have also been related to a neuroprotective effect by decreasing the expression of Aβ peptides and improved the paralysis and lifespan in a C. elegans model of AD [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibited AChE and monoamine oxidase A [49] In addition, when compared with other matrices such as fruit, flowers such as marigold (Tagetes erecta) [61] and E. elatior [18] showed higher chlorogenic acid content when compared to Mulberries fruit extract (0.136-0.517 mg / g) [33]. This information indicates the high potential of edible flowers to be a neuroprotective agent.…”
Section: In Vitro Enzyme Inhibitorymentioning
confidence: 88%
“…Phenolic acid, such as syringic acid, salicylic acid, chlorogenic acid from Butea monosperma and Sesbania grandiflora inhibit the enzymes AChE and BuChE which leads to prevent the breakdown of acetylcholine, so that the acetylcholine content in the nerves does not decrease [17]. Viola wittrockiana flower is also known to inhibit AChE and monoamine oxidase A [49]. This inhibitory activity may be due to the high content of quercetin and other flavonoids such as anthocyanin.…”
Section: Neuroprotective Agentmentioning
confidence: 99%